All Days 2012
DOI: 10.2118/157119-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Flow Assurance Using Co-Ni Nanoparticles For Dewaxing Of Production Tubing

Abstract: The most frequent problem encountered in day to day oil well production is the deposition of paraffin or wax inside the production tubing. The solution to this problem is frequent scraping and hot oil operation with help of Coiled Tubing Unit (CTU) thereby increasing the non productive time. The following paper proposes an alternative technique for dewaxing of production tubing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Some studies have investigated the effects of various factors, such as asphaltene and water content, temperature and contact time on the asphaltene adsorption onto NP surfaces [56,57]. The results showed that the extent of asphaltene adsorption onto the NPs increased with increasing the contact time.…”
Section: Preventing Asphaltene Precipitationmentioning
confidence: 99%
“…Some studies have investigated the effects of various factors, such as asphaltene and water content, temperature and contact time on the asphaltene adsorption onto NP surfaces [56,57]. The results showed that the extent of asphaltene adsorption onto the NPs increased with increasing the contact time.…”
Section: Preventing Asphaltene Precipitationmentioning
confidence: 99%
“…Asphaltene adsorption onto the nanoparticles surface is spontaneous and exothermic [27]. Some experiments have been done to examine the effect of various parameters such as contact time, Initial asphaltene content, temperature, and water content on the asphaltene adsorption onto the nanoparticles surface [28,29]. The greater the contact time, the more the asphaltene adsorption onto the nanoparticles takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Increase of the temperature of tubing causes the wax melts and flows [29]. Greff and Babadagli stated that, metal nanoparticles are effective in breaking the bonds between the carbon and sulfur atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Haindade provided a new technique, which involves the use of Co-Ni nanoparticles along with an exclusive polymer to be pumped inside the annulus between production tubing and casing at the time of well commissioning (Haindade et al, 2012). The nanoparticles remain suspended in the polymer filled inside the annulus throughout the life of the well.…”
Section: Paraffin Inhibitionmentioning
confidence: 99%